Public and community conservation of biodiversity — rivalry or cooperation? - Lenka Slavíková; Zdenka Smutná; Marta Žambochová; Vladislav Valentinov (GeoScape, 2020)
Although private or community initiatives for biodiversity conservation (such as land trusts) have a strong tradition in many countries, rigorous evidence of recently evolved movements in post-socialist countries is missing. This study describes the evolution of Czech land trust movement and analyses their representatives' motivation for engagement in biodiversity conservation. It also investigates the intensity of interaction among public and land trust conservation efforts. For this purpose, we identified localities in which the territory managed by Czech land trusts overlaps with small-scale public nature reserves managed by regional governments. We conducted semi-structured face-to-face interviews with representatives of all NGOs and regional officials in-charge. Our qualitative analysis revealed that some regional biodiversity conservation officials see land trusts as partners, but others are rather indifferent to, or uninformed about, their activities. Additionally, land trust representatives see themselves as complementing the public effort: their main motivation for engagement is to facilitate biodiversity conservation in addition to the public provision.
Keywords: 330; biodiversity conservation; cooperation; community; NGOs; land trust; Czechia